Randomized Phase II Trial of Irinotecan/Docetaxel or Irinotecan/Docetaxel Plus Cetuximab for Metastatic Pancreatic Cancer: An Eastern Cooperative Oncology Group Study. (August 2016) - Burtness, Barbara; Powell, Mark; Catalano, Paul; Berlin, Jordan; Liles, Darla K.; Chapman, Andrew E.; Mitchell, Edith; Benson, Al B.
Abstract : Objectives: The primary objective was to determine the response rate in patients with metastatic pancreatic cancer treated in first line with irinotecan/docetaxel combination (Arm A) or with irinotecan/docetaxel/cetuximab combination (Arm B). Secondary endpoints were progression-free survival (PFS), overall survival (OS), toxicity, and the rate of thromboembolic events with prophylactic enoxaparin sodium. Patients and Methods: Patients were eligible who had measurable, metastatic adenocarcinoma of the pancreas, and normal bilirubin. All patients received anticoagulation. Docetaxel (35 mg/m 2 ) and irinotecan (50 mg/m 2 ) were administered once a week for 4 weeks followed by 2 weeks rest (Arm A) alone or with the addition of cetuximab (Arm B). The primary endpoint was response rate. Results: A total of 87 eligible patients were enrolled and treated. Grade 3/4 toxicity was observed in 74% of patients in Arm A and 76% in Arm B. The principal grade 3/4 toxicity was diarrhea. Response rates were 4.5% in Arm A and 7% in Arm B. Median PFS and OS were 3.9 and 6.5 months in Arm A and 4.5 and 5.4 months in Arm B. Conclusions: Docetaxel/irinotecan combination is associated with considerable toxicity. Objective responses were infrequent and addition of cetuximab in an unselected population was not beneficial, but PFS and OS were comparable with those achieved with other regimens. Docetaxel/irinotecan therapy is active in metastatic pancreatic cancer.